An innovation of packaging with handle rope for baju kurung batik using the implementation of augmented reality and QR code / Nurhaziqah Azmi ... [et al.] - Azmi, Nurhaziqah; Omar, Mastura; Mohd Rosnan, Shalida; Abu Daud, Jamil Iswan; Masod, Muhammad Yusuf (Universiti Teknologi MARA, Kedah, 2023)
According to Encik Fahmim Bin Daros, Empayar Batik Exclusive was established on 2 October 2015. This company Empayar Batik Exclusive sells variety of ‘’batik’’ with many patterns but I am more interested in producing packaging for baju kurung batik. If the product has packaging, it will improve the branding of the company and make the product look exclusive. Packaging is a container and wrapping materials used to protect, contain, identify, promote, and facilitate the use of the product. Packaging is also an essential part of marketing strategies because it makes a product more attractive to consumers' eyes and improves the probability that it will be chosen over the other. The innovation packaging with handle rope for baju kurung batik, as a marketing strategy is the best method in attracting consumers to buy the products because it exists the handling rope at the top will making it easier for the consumers to hold and bring the product to everywhere. In addition to producing attractive packaging, adding a handle rope to the box packaging raises the level and standards of the products. The innovation of this packaging also combined with the innovation of Augmented Reality and QR code, so customers and consumers can easily get additional information of the baju kurung batik. When scanning Augmented Reality, customers can scan the image flower on the front packaging to watch the video process of drawing batik. Qr Code is also an innovation in packaging, it functions to provide details about the product. I put Qr Code linktree. Linktree is a tool that can share one direct link to an array of products batik. When scanning the Qr Code, it will go to the linktree and it displays list which have boutique maps, sale on tiktok and whatsapp. This is to make it easier for customers when they scan the Qr Code then can see the three different profile social media with use linktree.